The role of resistance exercise in improving mobility in patients with Non-Communicable Chronic Diseases (NCDS) (Research, Society and Development, 2025)
Introduction: Chronic Non-Communicable Diseases (NCDs), such as cardiovascular diseases, cancer, diabetes, and chronic respiratory problems, represent one of the leading causes of disease and death worldwide. Objective: to identify how resistance exercise can contribute to improving the mobility of patients with chronic non-communicable diseases (NCDs), and its impact on quality of life. Methodology: a mixed descriptive study of integrative literature review, with a qualitative-quantitative approach. Data collection was carried out in academic databases, such as PubMed, SciELO, Google Scholar and Web of Science, selecting 15 articles published in the last 10 years (2015 to 2025), in Portuguese and English. Results: The results showed that resistance training promoted significant gains in muscle strength (18-28%), improved functional mobility (12-20%), reduction of symptoms associated with NCDs (9-15%) and significant increase in quality of life (15-20%). Conclusion: In view of these results, it is recommended that health promotion programs aimed at populations with NCDs incorporate regular resistance training routines, adapted to individual needs and associated, whenever possible, with aerobic exercises and health education strategies.